Meningiomas in three male‐to‐female transgender subjects using oestrogens/progestogens and review of the literature. (16th February 2016) - ter Wengel, P. V.; Martin, E.; Gooren, L.; Den Heijer, M.; Peerdeman, S. M.
Summary: Sex hormones have been proposed as a possible risk factor for the development and growth of meningiomas. Hormonal therapy plays a fundamental role in the treatment of male‐to‐female transgenders and needs to be continued after sex reassignment surgery. Usually, this treatment leads to no adverse events; however, its impact on hormone‐related tumours such as meningiomas has not yet been investigated thoroughly. We searched our cohort of 2810 male‐to‐female transgender persons, who have been treated between 1975 and 2010, for patients with meningiomas. Additionally, we conducted a literature search in PubMed and EMBASE. We found three patients who developed a meningioma in male‐to‐female transgenders in addition to five other who have been described in the literature. These findings support the role of female sex hormones in the development and growth of meningiomas. This might be an underrepresentation, because there is no standard protocol for screening for meningiomas in this population and meningiomas can remain asymptomatic for several years. We observed regression of multiple meningiomas in one of these three cases after discontinuation of hormonal treatment. The decision to stop or continue cross‐sex hormone therapy in these particular patients should be carefully reconsidered individually.